Complete imperforate tranverse vaginal septum with septate uterus: A rare anomaly - Nutan Jain; Anjali Gupta; Ravindra Kumar; Agnes Minj (Wolters Kluwer Medknow Publications, 2013)
The isolated, complete, transverse vaginal septum is one of the most infrequent anomalies of the female genital tract, and when it coexists with a septate uterus, it is even rarer. This report describes a case of transverse vaginal septum with septate uterus. A 12-year-old girl sought medical assessment because of severe cyclic lower abdominal cramping and pelvic pain. Local examination revealed a blind vaginal pouch of 2 cm and on rectal examination a tender pelvic mass was noted. Radiological examination showed transverse vaginal septum in the lower vagina with bicornuate uterus. Surgical resection of the vaginal septum was done under laparoscopic guidance. Hysteroscopy revealed presence of uterine septum which was resected by a resectoscope. Post-operative dilatation of vagina was done to prevent restenosis. Laparoscopic guided abdominoperineal approach is better in such a case as multiple mullerian anomalies may coexist with each other.